STRATEGIES FOR THE DEVELOPMENT OF COMMUNITY-BASED ECOTOURISM IN THE TRADITIONAL VILLAGE OF RATENGGARO, SOUTH-WEST SUMBA REGENCY, TO BOOST LOCAL REVENUE (PAD) - Marcela Jenifer Peso; Cicilia Apriliana Tungga; Muhammad Alwan Habibi Mushlih (Universitas Dharmawangsa Medan, 2026)
This study aims to formulate a community-based ecotourism development strategy and analyse the role of stakeholders in the Ratenggaro Traditional Village as a sustainable tourism destination in Maliti Bondo Ate Village, Kodi Bangedo District, Southwest Sumba Regency. Ratenggaro Traditional Village possesses the potential for stunning natural beauty, a strategic location and a rich local culture. However, its management has not been optimal, particularly due to a lack of facilities and inadequate infrastructure. This study employs a qualitative approach, utilising descriptive analysis and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to determine the strategic positioning and formulate policy recommendations. The results of the SWOT analysis indicate that the strategic positioning of Ratenggaro Traditional Village falls within Quadrant I (aggressive strategy), signifying that it possesses significant internal strengths and faces substantial external opportunities; consequently, the appropriate strategy is an aggressive growth strategy. The conclusion of this study indicates that the development of Ratenggaro Traditional Village requires the active involvement of stakeholders in creating high-quality activities, facilities, services and experiences, as well as ensuring that tourism benefits are channelled to provide advantages for both the community and the environment. Recommended strategic policies include the development of community-based ecotourism supported by the local government, increased promotion via digital media, the construction of public facilities, and the establishment of formal management structures to ensure sustainability. The implementation of these strategies is expected to increase visitor numbers and length of stay, which will directly strengthen the local economy and contribute to regional tax revenue, thereby boosting local revenue (PAD).